The Role of Satisfaction in Mediating The Effect of Cashback Promotions and Ease of Use On Customer Loyalty of Ovo E-Wallet In Denpasar City - Ni Kadek Eristya Handayani; Ni Made Rastini (Universitas 45 Surabaya, 2025)
The development of online transactions in the digitalization era has driven the growth of financial technology, including e-wallets or digital wallets. OVO is a widely used e-wallet that has experienced rapid growth after collaborating with Grab and Tokopedia. This study aims to explain the role of satisfaction in mediating the effect of cashback promotions and ease of use on customer loyalty of the OVO e-wallet in Denpasar City. The research was conducted in Denpasar City, with a population consisting of Denpasar residents who have actively used the OVO e-wallet for the past six months. A total of 100 respondents were selected using a purposive sampling technique. Data collection was carried out through questionnaires distributed both offline and online via Google Forms. The data were analyzed using descriptive analysis and path analysis with a significance level of 5% using SPSS version 26.0. The hypothesis testing results indicate that cashback promotions have a positive and significant effect on customer loyalty. Ease of use has a positive and significant effect on customer loyalty. Satisfaction has a positive and significant effect on customer loyalty. Cashback promotions have a positive and significant effect on satisfaction. Ease of use has a positive and significant effect on satisfaction. Satisfaction plays a positive and significant role in mediating the effect of cashback promotions on customer loyalty. Satisfaction also plays a positive and significant role in mediating the effect of ease of use on customer loyalty. The theoretical implications of this study provide evidence for the development of consumer behavior studies and marketing management. The practical implications of this study are expected to serve as a consideration and input for OVO e-wallet companies in improving customer loyalty. Future researchers are encouraged to expand the scope of the study.